2018
DOI: 10.1093/humrep/dey262
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic testing for aneuploidy by microarray analysis of polar bodies in advanced maternal age: a randomized clinical trial

Abstract: 25 June 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 37 publications
4
68
0
1
Order By: Relevance
“…ESTEEM involved 396 patients aged 36–40 years with good ovarian reserve and tested whether PGT‐A by PBB would improve the chances of a live birth within 1 year. Both groups achieved the same pregnancy rate (24%) and PGT‐A did not shorten the time to pregnancy . However, PGT‐A reduced miscarriage from 14% to 7% ( P = 0.02) and increased the number of SETs (19% vs 56%; P < 0.001) with a corresponding trend toward reduced twins …”
Section: Pgt‐a Outcomes By Intention‐to‐treat Analysesmentioning
confidence: 86%
See 1 more Smart Citation
“…ESTEEM involved 396 patients aged 36–40 years with good ovarian reserve and tested whether PGT‐A by PBB would improve the chances of a live birth within 1 year. Both groups achieved the same pregnancy rate (24%) and PGT‐A did not shorten the time to pregnancy . However, PGT‐A reduced miscarriage from 14% to 7% ( P = 0.02) and increased the number of SETs (19% vs 56%; P < 0.001) with a corresponding trend toward reduced twins …”
Section: Pgt‐a Outcomes By Intention‐to‐treat Analysesmentioning
confidence: 86%
“…More recently, results of the ESTEEM (the ESHRE Study into the Evaluation of oocyte Euploidy by Microarray analysis) trial based on polar body biopsy (PBB) were reported . ESTEEM was a multicentre trial involving nine centres in seven countries in Europe and Israel having experience in PBB . ESTEEM involved 396 patients aged 36–40 years with good ovarian reserve and tested whether PGT‐A by PBB would improve the chances of a live birth within 1 year.…”
Section: Pgt‐a Outcomes By Intention‐to‐treat Analysesmentioning
confidence: 99%
“…However, fewer embryo transfers were required following aneuploidy screening, and fewer miscarriages occurred to achieve the same LBR as the control group. Of note, 24 % of patients in the PBB group had no fresh embryo transfer after ART while in the control group this figure was only 7 % [11].…”
Section: Introductionmentioning
confidence: 92%
“…This largely results from the fact that the original trials did not report the cumulative live birth rate, but instead reported the live birth rate per fresh transfer. The recently published ESTEEM (The ESHRE study into the evaluation of oocyte euploidy by microarray analysis) trial selected embryos based on the PGT‐A results of a first and second polar biopsy using comprehensive chromosome screening, and showed that this method did not increase the cumulative live birth rate . Nevertheless, these embryo selection techniques have been used widely in clinical practice before solid evidence was available.…”
Section: Limitations Of the Evidence On Embryo Selection Techniquesmentioning
confidence: 99%